Synthesis and Characterization of Copper Oxide Compounds. Issue 1633 (2014) - Hering, K.P.; Polity, A.; Kramm, B.; Portz, A.; Meyer, B.K.
ABSTRACT: The p-type conducting Copper-oxide compound semiconductors (Cu2 O, CuO) provide a unique possibility to tune the band gap energies from 2.1 eV to the infrared at 1.40 eV into the middle of the efficiency maximum for solar cell applications. By a pronounced non-stoichiometry the electronic properties may vary from insulating to metallic conduction. They appear to be an attractive alternative absorber material in terms of abundance, sustainability, non-toxicity of the elements, and numerous methods for thin film deposition that facilitate low cost production. The synthesis and characterization of Cu2 O thin films used as p-type absorbers in heterojunction solar cells will be reported. We discuss properties of the undoped non-stoichiometric Cu2 O, controlled p-type doping by nitrogen, analysis of band offsets by X-ray photoelectron spectroscopy (XPS). In addition we show proof of concept for an increase in photovoltaic conversion efficiency in AlGaN/Cu2 O heterostructures due to a more favorable band alignment.